2017
DOI: 10.1007/s10388-017-0570-z
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium after pharyngolaryngectomy with esophagectomy: a role for ramelteon and suvorexant

Abstract: BackgroundPostoperative delirium is common after extensive surgery, and is known to be associated with sleeping medications. In this study, we aimed to investigate the relationships between sleeping medications and postoperative delirium after pharyngolaryngectomy with esophagectomy.MethodsWe performed a retrospective analysis of 65 patients who underwent pharyngolaryngectomy with esophagectomy at Shizuoka Cancer Center Hospital between January 2012 and March 2016. All data were assessed by two psychiatrists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 10 publications
0
42
0
Order By: Relevance
“…Melatonin dose was 3 mg in 4 studies, 27‐29,31 5 mg in 2 studies 30,33 and 50 mg/kg in 1 study 32 . Ramelteon dose was 8 mg in the remaining 2 studies 34,35 . The diagnostic tools for delirium were different among these studies.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Melatonin dose was 3 mg in 4 studies, 27‐29,31 5 mg in 2 studies 30,33 and 50 mg/kg in 1 study 32 . Ramelteon dose was 8 mg in the remaining 2 studies 34,35 . The diagnostic tools for delirium were different among these studies.…”
Section: Resultsmentioning
confidence: 98%
“…From these, 10 records were excluded due to the following reasons: 9 for conference abstracts and 1 for reporting tryptophan supplementation with no difference in the postoperative serum melatonin levels 26 . Finally, 6 randomized controlled trials, 27‐32 2 cohort studies 33,34 and 1 case‐control study 35 were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of study subjects were patients in acute care general wards (64%), while a minority (36%) of patients were in the ICU . A single‐centre retrospective observational study by Booka et al, showed that the use of suvorexant combined with ramelteon was associated with a decrease in postoperative delirium, but the only patients included in the study were those who had undergone pharyngolaryngectomy with esophagectomy . Another randomized control study by Hatta et al, showed that suvorexant had protective effects against delirium in acute care wards and ICU, but all intubated patients were excluded .…”
Section: Discussionmentioning
confidence: 99%
“…5 A single-centre retrospective observational study by Booka et al, showed that the use of suvorexant combined with ramelteon was associated with a decrease in postoperative delirium, but the only patients included in the study were those who had undergone pharyngolaryngectomy with esophagectomy. 9 Another randomized control study by Hatta et al, showed that suvorexant had protective effects against delirium in acute care wards and ICU, but all intubated patients were excluded. 10 In contrast to these studies, the present study was conducted only in an ICU, almost exclusively with intubated patients (Table 2).…”
Section: Discussionmentioning
confidence: 99%